The Influence of Job Satisfaction and Job Loyalty of Employees (Sewing Operator) on Employee Performance at PT. Sansan Saudaratex Jaya Cimahi - Rosadin, Andri Asoka Sidantara; Gulo, Time Kristiani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Employee performance is a result achieved by a person in carrying out the tasks assigned to him. This study aims to determine the effect of job satisfaction and employee loyalty on the performance of employees at PT. Sansan Brothertex Jaya Cimahi. The research method used in this study is a descriptive and associative method with the help of the SPSS 25 application. In this study, the unit of analysis was the sewing operator at PT. Sansan Brothertex Jaya Cimahi. The results of this study indicate that the variable job satisfaction contributes or influences employee performance by 39.0%, and employee loyalty (sewing operator) contributes or influences employee performance by 18.7%. And simultaneously the variables of job satisfaction and employee loyalty (sewing operators) have an influence on employee performance of 57.7%.